Critical Synthesis Package: Stanford Presenteeism Scale (SPS-6) - Elizabeth McClain (Association of American Medical Colleges, 2013)
Abstract This Critical Synthesis Package contains: (1) a Critical Analysis of the psychometric properties of the Stanford Presenteeism (SPS-6) and 2) a copy of the SPS-6 instrument and the scoring instructions developed by Cheryl Koopman, PhD. The SPS-6 evaluates the impact of health problems on individual work performance and overall perceived productivity for knowledge-based activity. The SPS-6 results are utilized for monitoring and measurement of interventions and improvement of employee health status and productivity. The SPS-6 targets the general working population with more than a high-school education. This 6-item instrument is not norm referenced or standardized, but higher scores are associated with higher presenteeism or a greater perceived ability to concentrate on and accomplish work despite health problems. This instrument has good psychometric properties and is emerging as a tool for assessing the effectiveness of employee health and wellness interventions attempting to address changes in presenteeism for medical residents. It may also be used to measure the impact of chronic illness and mental health problems on presenteeism. Although the SPS-6 items possess good psychometric properties, further studies are needed to establish further validation, substantiate more consistent internal reliability, and clear the utility of this instrument across different work populations